Development of Virtual Laboratory Simulation: e-SCILAB on Waves for Grade 7 Science - Tongco, John; Silvederio, Wesley Clarke; Salanawon, Pamela Joy; Mercado, Justine (Future Science / FSH-PH Publications, 2021)
Virtual Laboratory Simulation (VLS) enhances student understanding, retention of concepts, and promotes active learning through direct visualization and manipulation of computer animations. This study aimed to develop a VLS with complementary manual for Grade 7 physics that can be utilized by the teachers to address the needs of the students in the new normal learning. The developed VLS is composed of a Teacher’s Instructional Manual and Student’s Learning Manual. The study used Research and Development approach with the ADD (Analysis, Design, and Development) model as the instructional method. These allows the researchers to analyze the need of VLS, identify the design of VLS, and develop the VLS. The VLS was evaluated based on the content quality with a mean of 4.68, technical quality with 4.65, and instructional quality with 4.57. The results for the complementary activity manual in terms of the content quality is a mean of 4.62, the technical quality with 4.54, and the instructional quality with 4.55. The result showed that the developed VLS together with the complementary activity manual satisfied the quality components and attained the intended standards. It is recommended that evaluation of the effectiveness of VLS through pilot tests in public and private schools.